2018
DOI: 10.1039/c8ob00030a
|View full text |Cite
|
Sign up to set email alerts
|

C8-Guanine modifications: effect on Z-DNA formation and its role in cancer

Abstract: Base modifications are known to affect the structure and function of DNA. C8-guanine adducts from various carcinogenic compounds have been shown to be potent Z-DNA inducers. Hence, it has been hypothesized that Z-DNA plays a role in cancer and other genetic diseases. In this comprehensive review, Z-DNA and the effect of prevalent C8-guanine adducts on the B-Z transition are addressed. The discoveries of Z-DNA binding proteins including ADAR1, E3L, DLM1, and PKZ have suggested the relevance of Z-DNA in living s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 112 publications
0
16
0
Order By: Relevance
“…Investigation of the Z‐DNA conformations associated with biological events in living cells is essential as a means to understand the functions of Z‐DNA. However, obtaining a stable Z‐form structure from native oligonucleotides under physiological salt conditions is difficult because the structure usually requires molar concentrations of inorganic salt to overcome the unfavorable electrostatic interactions from the phosphate groups (Balasubramaniyam et al., 2019; Vongsutilers & Gannett, 2018; Xu et al., 2003). Also, molecular probes for the observation of the structure of Z‐DNA inside living cells has not yet been developed.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of the Z‐DNA conformations associated with biological events in living cells is essential as a means to understand the functions of Z‐DNA. However, obtaining a stable Z‐form structure from native oligonucleotides under physiological salt conditions is difficult because the structure usually requires molar concentrations of inorganic salt to overcome the unfavorable electrostatic interactions from the phosphate groups (Balasubramaniyam et al., 2019; Vongsutilers & Gannett, 2018; Xu et al., 2003). Also, molecular probes for the observation of the structure of Z‐DNA inside living cells has not yet been developed.…”
Section: Commentarymentioning
confidence: 99%
“…It is therefore of great importance to investigate Z‐DNA structures associated with biological events as a means to further understand the functions of these molecules. However, it is difficult to obtain stable Z‐form structures from native oligonucleotides under physiological salt conditions because the Z‐DNA structure usually requires molar concentrations of inorganic salt to overcome the unfavorable electrostatic interactions of the phosphate groups (Balasubramaniyam, Ishizuka, Xiao, Bao, & Xu, 2019; Vongsutilers & Gannett, 2018; Xu, Ikeda, & Sugiyama, 2003). We recently demonstrated a novel synthesis and application of a base modification, 8‐trifluoromethyl‐2′‐deoxyguanosine ( CF3 dG), as a Z‐DNA‐promoting modification and a tool for Z‐DNA detection in vitro and in HeLa cells by 19 F NMR spectroscopy (Bao, Masuzawa, Oyoshi, & Xu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, magnesium may act as a double-edged sword in carcinogenesis. It has been demonstrated that high concentrations of magnesium may induce conformational changes from B-DNA to Z-DNA, which may contribute to gene dysregulation, which is correlated with carcinogenesis [27, 28]. Previous studies have reported that higher intracellular magnesium levels may promote tumor cell proliferation [7, 26].…”
Section: Discussionmentioning
confidence: 99%
“…These biological structures can also undergo conformational changes under different physiological conditions. Although the canonical DNA structure is a right‐handed duplex (B‐DNA), B‐DNA with alternating purine–pyrimidine sequences can conformationally change to a left‐handed duplex (Z‐DNA) due to various factors, such as high ionic strength, protein binding, small molecule binding, and chemical modifications . The B‐ to Z‐DNA transition, which plays a crucial role in biological systems, has been utilized for nanomechanical devices and nanosensors .…”
Section: Introductionmentioning
confidence: 99%